Retention of visa-trainee post-graduate residents in Canada: a retrospective cohort study - Maria Mathews; Dania Koudieh; Yanqing Yi; Lindsay Hedden; Emily Gard Marshall; Asoka Samarasena; Geoff Barnum; Ivy Bourgeault (BMC, 2021)
Abstract Background Visa trainees (international medical graduates [IMG] who train in Canada under a student or employment visa) are expected to return home after completing their training. We examine the retention patterns of visa trainee residents funded by Canadian (regular ministry and other), foreign, or mixed sources. Methods We linked data from the Canadian Post-MD Medical Education Registry with Scott's Medical Database for a retrospective cohort study. Eligible trainees were IMG visa trainees as of their first year of training, started their residency program no earlier than 2000, and exited training between 2006 and 2016. We used Cox regression to compare the retention of visa trainees by funding source. Results Of 1,913 visa trainees, 431(22.5%), 1353 (70.7%) and 129 (6.8%) had Canadian, foreign, or mixed funding, respectively. The proportion of trainees remaining in Canada decreased over time, with 35.5% (679/1913); 17.7% (186/1052); 10.8% (11/102) in Canada one, five, and ten years, respectively after their exit from PGME training. Trainees who remained on visas (HR: 1.91; [95% CI 1.59, 2.30]), were funded exclusively by foreign sources (HR: 1.46; [95% CI 1.25, 1.69]), and who had graduated from 'Western' countries (HR: 1.39; [95% CI 1.06, 1.84]) were more likely to leave Canada compared to trainees who became citizens/permanent residents, were funded by Canadian sources, or were visa graduates of Canadian medical schools, respectively. Conclusions Most visa trainees leave Canada following their training. Trainees with Canadian connections (funding and/or change in legal status) were more likely to remain in Canada.